Infection with an Avirulent phoP Mutant of Neisseria meningitidis Confers Broad Cross-Reactive Immunity - Newcombe, J. (American Society for Microbiology, 2004)
Successful vaccines against serogroup A and C meningococcal strains have been developed, but current serogroup B vaccines provide protection against only a limited range of strains. The ideal meningococcal vaccine would provide cross-reactive immunity against the variety of strains that may be encountered in any community, but it is unclear whether the meningococcus possesses immune targets that have the necessary level of cross-reactivity. We have generated a phoP mutant of the meningococcus by allele exchange. PhoP is a component of a two-component regulatory system which in other bacteria is an important regulator of virulence gene expression. Inactivation of the PhoP-PhoQ system in Salmonella leads to avirulence, and phoP mutants have been shown to confer protection against virulent challenge. These mutants have been examined as potential live attenuated vaccines. We here show that a phoP mutant of the meningococcus is avirulent in a mouse model of infection. Moreover, infection of mice with the phoP mutant stimulated a bactericidal immune response that not only killed the infecting strain but also showed cross-reactive bactericidal activity against a range of strains with different serogroup, serotype, and serosubtyping antigens. Sera from the mutant-infected mice contained immunoglobulin G that bound to the surface of a range of meningococcal strains and mediated opsonophagocytosis of meningococci by human phagocytic cells. The meningococcal phoP mutant is thus a candidate live, attenuated vaccine strain and may also be used to identify cross-reactive protective antigens in the meningococcus.